VISIBLE ELEMENTS OF COVID 19 REPSERENTATIONS: AESTHETICIZATION OF THE CORONAVIRUS’ BLACK SUN - Tomanovic, Violeta; Cvetkovski, Tatjana (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2022)
Summary: The paper deals with the Covid 19 iconology research, from the beginning of the pandemic at the end of 2019 to the end of 2021. The task of the paper is to determine the way of creating a visible image of the invisible “enemy” and designing stable collective representations. The paper discusses the relationship between black and white images and color images, as well as the relationship between scientific images and stylized, aestheticized and inaccurate coronavirus representations, which enabled the virus, invisible to the eye, to become conceivable globally. The hypothesis of this paper is that mediated reality is transmitted and shaped through visual symbols and coronavirus representations. Although many authors have given their opinion on the uniformity of the coronavirus icon and hence its adaptability in different contexts, the authors of this paper claim that the basic representations of the virus media circulation is the archetypal symbol of the Sun, specifically the Black Sun. The paper also analyzes the content through the example of the photography that appears 109 times on the official Government of Serbia internet web page on the Kovid 19 topic, in English, from March 6 2020 to 9 December 2021, and thus, bears different titles. The conclusion of the paper is that the image-icon, the symbol of coronavirus, mainly represents an aestheticized form of real danger and therefore significantly mitigates it, while on the other hand it plays with the archetype of the Sun or Black Sun through its dual nature, i.e. death and transformation. Keywords: Coronavirus, Covid 19, icon, archetype, science, media, symbol, Sun.